Characterization of sputter-deposited 316L stainless steel films - Godbole, M. J.; Pedraza, A. J.; Allard, L. F.; Geesey, Gill G. (My University, 1992)
Sputter-deposited 316L stainless steel films deposited on various substrates were characterized using transmission electron microscopy and X-ray diffractometry. The deposits were found to be fine-grained and the phases present in the films depended on the nature of the substrate. Films of various thicknesses deposited on microscope slides or oxidized stainless steel substrates contained a mixture of two phases: a body centre cubic (b c c) and a modified hexagonal ε-phase. The hexagonal phase appeared to be an ordered phase, as suggested by the aO value of the structure, which is twice that for the ε-martensite found in many deformed stainless steels. These films were hard and brittle, as indicated by microhardness measurements. Films deposited on oxide-free austenitic stainless steel substrates, on the other hand, were mostly b c c and exhibited a dominant 〈2 00〉 texture. These films were softer and less brittle than those deposited on oxidized substrates. In situ high-temperature X-ray diffractometry revealed that the ε-phase transformed to b c c when the films were annealed at 773 K. On annealing at 873 K, the b c c phase transformed to face centre cubic, which remained stable on cooling to room temperature. These results agree with published data which suggest stability of the b c c phase up to 840 K. Some discrepancies from earlier published reports are discussed in the light of the present results.